Polarimetric Characteristics for Sea-Ice Surface Topographic Derivation Using TanDEM-X Interferometry Data - Lanqing, Huang; Hajnsek, Irena; Nghiem, Son (IGARSS 2020 - 2020 IEEE International Geoscience and Remote Sensing Symposium, 2020)
Interferometric synthetic aperture radar (InSAR) is an effective technique for sea-ice topographic retrieval. However, the penetration of electromagnetic waves into snow-covered thick ice limits the accuracy of InSAR-derived sea-ice topography. In this study, the data were acquired over the sea ice in the western Weddell Sea, Antarctica. A new method is proposed by merging co-polarization coherence into InSAR processing to measure the sea-ice surface topography.